Effects of trypanocidal drugs on DNA synthesis: new insights into melarsoprol growth inhibition. Issue 10 (17th September 2021) - Larson, Stephen; Carter, McKenzie; Hovel-Miner, Galadriel
Abstract: Abstract: Trypanothione is the primary thiol redox carrier in Trypanosomatids whose biosynthesis and utilization pathways contain unique enzymes that include suitable drug targets against the human parasites in this family. Overexpression of the rate-limiting enzyme, γ -glutamylcysteine synthetase (GSH1), can increase the intracellular concentration of trypanothione. Melarsoprol directly inhibits trypanothione and has predicted the effects on downstream redox biology, including ROS management and dNTP synthesis that require further investigation. Thus, we hypothesized that melarsoprol treatment would inhibit DNA synthesis, which was tested using BrdU incorporation assays and cell cycle analyses. In addition, we analysed the effects of eflornithine, which interfaces with the trypanothione pathway, fexinidazole, because of the predicted effects on DNA synthesis, and pentamidine as an experimental control. We found that melarsoprol treatment resulted in a cell cycle stall and a complete inhibition of DNA synthesis within 24 h, which were alleviated by GSH1 overexpression. In contrast, the other drugs analysed had more subtle effects on DNA synthesis that were not significantly altered by GSH1 expression. Together these findings implicate DNA synthesis as a therapeutic target that warrants further investigation in the development of antitrypanosomal drugs.